Mortality from COVID-19 in the US: Did unions save lives? - Sergei Soares; Janine Berg (International Labour Organization (ILO), 2023)
This paper builds on the existing literature on the effect of unionization on OSH by providing an analysis of unionization's effects on COVID-19 mortality. It combines data from the NVSS with the CPS into a unique dataset. It finds that a 10 percentage-point increase in unionization is associated with a reduction in mortality from 26 per 100,000 workers to 24 per 100,000 workers. This means that if the United States had the union density of 35 percent that it had in 1954 instead of today's rate of 10 percent, the COVID-19 mortality rate for working people would have fallen from 26 to 19 per 100,000.
Keywords: 330; COVID-19